Menelusuri Hadhanah: Pemeriksaan Mendalam atas Kasus Hak Asuh Anak di Pengadilan Agama - M. Khairul Arwani; Doni Dermawan; Sarah Afifah (IDRIS Darulfunun Institute, 2023)
This paper reviews the practice of in-depth examination of child custody cases in the Religious Courts, focusing on the concept of Hadhanah. Hadhanah is an important principle in determining child custody decisions, where the best interests of the child take centre stage. The study identifies the examination process, including the involvement of the child in decision-making, as well as the role of experts and Witnesses in providing a detailed picture. Hadhanah inquiries highlight the complexity of resolving child custody struggles in the context of Islamic law. This research aims to find out what factors make Judges conduct on-site examinations related to child dispute cases. The method used is field research with a qualitative approach. Data was obtained using empirical approach and documentation. This research is expected to provide an in-depth understanding of the hadhanah deskente, and can serve as a guideline for educators, researchers, and stakeholders. The conclusion emphasises the importance of a holistic and sensitive approach to children's needs in the religious justice system.